Erythropoietin Dampens Injury-Induced Microglial Motility. Issue 8 (August 2015) - Mitkovski, Miso; Dahm, Liane; Heinrich, Ralf; Monnheimer, Mathieu; Gerhart, Simone; Stegmüller, Judith; Hanisch, Uwe-Karsten; Nave, Klaus-Armin; Ehrenreich, Hannelore
Traumatic brain injury causes progressive brain atrophy and cognitive decline. Surprisingly, an early treatment with erythropoietin (EPO) prevents these consequences of secondary neurodegeneration, but the mechanisms have remained obscure. Here we show by advanced imaging and innovative analytical tools that recombinant human EPO, a clinically established and neuroprotective growth factor, dampens microglial activity, as visualized also in vivo by a strongly attenuated injury-induced cellular motility.